The Mitochondrial Genome of the Sea Anemone Stichodactyla haddoni Reveals Catalytic Introns, Insertion-Like Element, and Unexpected Phylogeny - Steinar Daae Johansen; Sylvia I. Chi; Arseny Dubin; Tor Erik Jørgensen (Life, 2021)
A hallmark of sea anemone mitochondrial genomes (mitogenomes) is the presence of complex catalytic group I introns. Here, we report the complete mitogenome and corresponding transcriptome of the carpet sea anemone Stichodactyla haddoni (family Stichodactylidae). The mitogenome is vertebrate-like in size, organization, and gene content. Two mitochondrial genes encoding NADH dehydrogenase subunit 5 (ND5) and cytochrome c oxidase subunit I (COI) are interrupted with complex group I introns, and one of the introns (ND5-717) harbors two conventional mitochondrial genes (ND1 and ND3) within its sequence. All the mitochondrial genes, including the group I introns, are expressed at the RNA level. Nonconventional and optional mitochondrial genes are present in the mitogenome of S. haddoni. One of these gene codes for a COI-884 intron homing endonuclease and is organized in-frame with the upstream COI exon. The insertion-like orfA is expressed as RNA and translocated in the mitogenome as compared with other sea anemones. Phylogenetic analyses based on complete nucleotide and derived protein sequences indicate that S. haddoni is embedded within the family Actiniidae, a finding that challenges current taxonomy.